Prevalence, Associated Factors, and Survival Outcomes of Small-Cell Neuroendocrine Carcinoma of the Gynecologic Tract: A Large Population-Based Analysis - Pang, Li; Wang, Shizhuo (Frontiers in Medicine, 2022)
Small-cell carcinomas are highly malignant tumors with neuroendocrine function and which often occur in the lungs. Primary small-cell neuroendocrine carcinomas of the gynecologic tract are extremely rare. This study aimed to evaluate the prevalence of independent predictors related to the prognosis and overall survival of patients with small-cell neuroendocrine carcinomas of the gynecologic tract. Patients with gynecologic small-cell neuroendocrine carcinomas diagnosed between 1973 and 2015 were identified from the Surveillance, Epidemiology, and End Results database. Univariate and multivariate Cox risk regression analyses were performed to determine the independent predictors of overall survival. Overall survival was calculated using the Kaplan-Meier method, and the log-rank test was used for comparison. We included 515,393 eligible carcinomas in the present study; the prevalence of gynecologic small-cell neuroendocrine carcinomas was 0.121% (N=622). Multivariate analysis indicated that advanced age, stage III and IV cancer, and no chemotherapy treatment may be predictors of poor small-cell neuroendocrine cervical carcinoma prognosis. Stage III and IV cancer and lack of surgery, radiotherapy, or chemotherapy were identified as potential predictors of poor prognosis in patients with ovarian small-cell neuroendocrine carcinoma. Kaplan-Meier analysis suggested that the median survival was 19, 11, and 12 months for cervical, ovarian, and endometrial small-cell neuroendocrine carcinomas, respectively. The 1-, 3-, and 5-year overall survival rates were as follows: 58.8%, 31.4%, and 26.1%, respectively, for small-cell neuroendocrine cervical carcinoma; 46.3%, 23.5%, and 22.0%, respectively, for ovarian small-cell neuroendocrine carcinoma; and 49.4%, 29.4%, and 25.9%, respectively, for endometrial small-cell neuroendocrine carcinoma. Our findings indicate that comprehensive and individualized treatment of small-cell neuroendocrine carcinomas of the gynecologic tract may prolong patient survival, although further studies are required.